ANALISIS KEKERINGAN MENGGUNAKAN METODE PALMER DROUGHT SEVERITY INDEX (PDSI) SERTA DAMPAKNYA TERHADAP SISTEM IRIGASI SUBAK PADA DAERAH ALIRAN SUNGAI (DAS) PALUNG LOMBOK : indonesia - Syakirin (Universitas Majalengka, 2022)
Drought is a natural event that is very influential on the availability of water reserves in the soil, both needed for agricultural purposes and human needs. The Irrigation Areas (DI) conducted by the study are Pandanduri-Swangi, Rutus, Terara and Temusik which are located in the Palung River Basin. This Drought Analysis includes Analysis of Rainfall, Regional Rainfall, Evaporation, calculation of the drought of the Palmer Severity Index (PDSI) method. Then do a comparative study of the Planting Pattern, water management and water turn schedule. In this study, the calculation of drought was carried out at 17 Rainfall Stations (ARR) with input data coming from 6 Climate Stations (CR) conducted by Thiessen Polygon analysis. The results of the drought index for each Rainfall Station (ARR) are then analyzed using the ArcGIS Software isohyet method with the Inverse Distance Weighted (IDW) interepolation to obtain the drought value of the area in each Irrigation Area (DI) analyzed. In this study it was found that: i) Pandanduri-Swangi Irrigation Area which has an area of ​​4,593 hectares of irrigation has a fairly long level of drought between July and October. ii) The relationship between the drought index to the existing Planting Area where the correlation obtained is for the Pandanduri-Swangi, Rutus, Temusik and Terara Irrigation Areas (48%, 61%, 72%, and 73%). iii) Drought index for Debits The availability of existing water correlations is: i) For Pandanduri-Swangi, Rutus, Temusik and Terara Irrigation Areas are 40%, 48%, 71%, and 30%.